VEGETATIVE GROWTH AND YIELD RESPONSE OF NIGER (GUIZOTIA ABYSSINICA) TO LEAF-LITTER DUST OF LANTANA CAMARA - P. K. GANTAYET,; K. C. LENKA,; B. PADHY, (The Bioscan, 2011)
Experiments were conducted to identify the allelopathic effects of different concentrations of leaf-litter dust of Lantana camara on the vegetative growth parameters (development of total number of leaves per plant, height of the plant, total leaf area, leaf area index) and components of yield (production of number of heads per plant, production of seeds per head, weight of seeds, seed yield per plant) of niger (Guizotia abyssinica). The results obtained and data presented in the tables showed the concentration dependent poor vegetative growth and decreased trend of yield of the test crop. This study indicates that the allelochemicals released from the leaf-litter dust into the soil had the potential to inhibit physiological processes of niger plant there by suppressed the above parameters of the test crop.